Pengaruh Voucher Diskon, Kemudahan Penggunaan dan Customer Rating Terhadap Keputusan Pembelian Mie Gacoan Menggunakan Online Food Ordering Pada Gen Z Di Kota Malang - A, Samhan Kadimi; Nurhidayah, Nurhidayah; Suharto, M. Khoirul Anwarudin Broto (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This study aims to test and analyze the influence of three independent variables, namely the Discount Voucher Feature, Ease of Use, and Customer Rating, on the dependent variable, namely the Decision to Purchase Gacoan Noodles Using Online Food Ordering in Gen Z in Malang City. Data collection was carried out through the purposive sampling method by distributing a Likert scale questionnaire to 100 respondents who met the criteria. The collected data was then analyzed using multiple linear regression methods and hypothesis testing, which included the F test (simultaneous test) and the t test (partial test), with the help of IBM SPSS version 25 software. The results of the analysis show that simultaneously, or together, the three independent variables, namely the Discount Voucher Feature, Ease of Use, and Customer Rating, have a significant influence on the Purchase Decision on Mie Gacoan Using Online Food Ordering. This is indicated by a significance value of 0.001, which is smaller than the set significance level, which is 0.05. However, the results of the partial test show different findings. Ease of Use was found to have no significant influence on Purchase Decisions, with a significance value of 0.077, which was greater than 0.05. In contrast, the Discount Voucher and Customer rating variables were partially shown to have a positive and significant influence on Purchase Decisions, with a significance value of 0.001 each, both of which were smaller than 0.05. Keywords: Discount Vouchers, Ease of Use, Customer Rating, Purchase Decisions